4x=6(6-x)

Simple and best practice solution for 4x=6(6-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x=6(6-x) equation:


4x=6(6-x)

We simplify the equation to the form, which is simple to understand
4x=6(6-x)

Reorder the terms in parentheses
4x=+(+36-6x)

Remove unnecessary parentheses
+4x=+36-6x

We move all terms containing x to the left and all other terms to the right.
+4x+6x=+36

We simplify left and right side of the equation.
+10x=+36

We divide both sides of the equation by 10 to get x.
x=3.6

See similar equations:

| (9-v)(5v-4)=0 | | 3sin(2x)=3cos(x) | | (Y^1/6)^3 | | -3b-6=-3(b+3) | | -1/6x=15 | | 2s+5=22 | | -8(x+4)+3x+5=6x+7 | | 3log(2x-1)=6 | | 56=7/8x | | x^2+19=x^2-98 | | ln(4*x^5)=1.5 | | 12x^3-18x^2-8x+12=0 | | 6x^2-14x-28=0 | | 3x^2-9=-6x | | x/9=12/11 | | 5x-2+8x= | | y/2=59 | | 2n^2+11n+15=0 | | X^5+4kx-4k^2=0 | | (44x+33)-(16x-8)=-76 | | 6s^2-11s+4=0 | | 9x+4=-4+7x+14 | | 5x-32+5=6x+7 | | -7(3+1)=4(2t+6) | | (4b*4b)-8b-5=0 | | -6y+18x=24 | | 5(5x-6)=20x | | -5(a+7)=-20 | | 14=7(3r-5) | | 300y^2+20y+60=0 | | m^2+16m-4=0 | | 2x^2=38 |

Equations solver categories